Fato e valor em John Stuart Mill - Maciel, Everton Miguel Puhl (2018)
The general aim of this thesis is to demonstrate that John Stuart Mill did not perpetrate a naturalistic fallacy. This argument can be applied to naturalism in gen-eral, but there seems to be a limitation for it to be used on Mill's utilitarianism. We think it is possible to demonstrate that he had, in his connection between justice and utility, a valuable method for the establishment of rules and principles that work like a standard for the normativity of laws; yet it does not offer a definition of “good in natu-ral terms”. Facts and values need to be justified by a set of normative theories. Jus-tice is dependent of the coexistence between rules and principles, so it has a rela-tionship of value with the utilitarianism (as a fact). This shows us that justice’s protec-tive rules are worth making, if taking into account features that are required by many different social contexts, which provide valuable facts for the implementation and grounding of rules and principles. The letters between Mill and Comte show us to what degree the Londoner subscribed the naturalism to the positivism and the rea-sons why he chose an idea of stability, both from a qualitative and a quantitative point of view of a political theory. Therefore, he defined a very factual based democ-racy concept, a criteria of the modern liberalism, and the aim of ought-is for possible corrections. The unrestricted freedom of thought and discussion is another feature that triggers the prescriptive and descriptive elements of Mill's utilitarianism, intimate-ly connected to the representative democracy. The normative justification in this con-text, does not operate by the epistemological aspect, but by the political sense of public justification, addressed to the moral community, fallibilist and, therefore, adaptable. Let us suggest that Moore pointed out a special naturalistic fallacy de-manding a "proof" of the utilitarianism principle by the summum bonum analysis. We will try to demonstrate that such proof is not feasible and that Mill, who knew about it, chose the political way to establish a ground criterion for the normativity. Rawls, on the other hand, subscribed Mill's liberalism, because he thought it is valid theory to justify fair and free institutions. Both Mill and Rawls present compromising liberal el-ements in their theories, regarding fact-valuable features.